Innovation projects management: a systematic literature review - Catto, Sergio Luiz; Maccari, Emerson Antonio (Revista de Administração da UFSM, 2021)
Purpose: To highlight how the theme innovation unfolds within the scope of project management and how both have been addressed in scientific literature in the last two decades Methodology: This research is a Systematic Literature Review, where procedures were applied in the selection of articles in Scopus and Web of Science databases, for the identification and interpretation of the main publications on the topic in the scientific literature, seeking to understand its relevance and evolution the last twenty years. Findings: The obtained sample, based on the Web of Science (WoS) and Scopus databases, totaled 13 articles from different sectors and areas of knowledge, with a predominance of publications linked mainly to the research and development area, with greater progress in innovation projects. Practical Implications: This research contributes to improving the understanding of the benefits of the practice of managing innovation projects. Social implications: The findings of this research will contribute to the understanding of how the management of innovation projects can contribute to maximize success in the dealings practiced in these projects. And due to the particular characteristics of innovation, focus on management efficiency and focus on results. Originality: This research addresses current and very broad themes - project management and innovation - involving several disciplines (human and social capital, teams, strategy, conflict management, knowledge management, governance, innovation, integration, research and development, intellectual property, behavioral theory), in an unprecedented way and seeks to define the new paradigm of development called Innovation Project Management.